Artificial intelligence in business and decision making: Analysis of benefits and challenges for consultancy SMEs - Filippi, Emilia; Bannò, Mariasole; Nencini, Isabella Elisa (Piccola Impresa / Small Business, 2024)
Purpose. This study examines how consultancy SMEs that have not yet adopted AI judge its adoption and its use in business activities and specifically in decision making and perceive its advantages and disadvantages. Design/methodology/approach. We conducted four case studies and semi-structured interviews involving four consultancy SMEs that have not yet adopted AI. Findings. In the consultancy sector, AI may be applied in Customer Relationship Management, data analysis, training, and work support. However, AI may not be the best technological solution and competent people may be lacking. The use of AI in decision making is viewed with more caution: possible advantages (e.g., higher efficiency, work facilitation) are recognised, but some perceived disadvantages (e.g., ethical, privacy, and responsibility issues; distortions in the decision-making process) must be addressed. Practical and Social implications. AI can bring numerous benefits for consultancy SMEs, which must be aware of the potential disadvantages. Policy makers should design effective interventions that support and guide these firms in adopting AI. Originality of the study. This study focused on consultancy SMEs, which may encounter difficulties in the introduction of AI due to insufficient resources and knowledge, while at the same time being pushed by the consultancy sector to urgently incorporate AI.